Research on the Application of Game Teaching in Primary School Music Classroom - Xu, Ming (Journal of Theory and Practice in Humanities and Social Sciences, 2024)
With the continuous development of society in recent years, we have gradually realized the importance of cultivating the all-round development of morality, intellect, physique, aesthetics and labor for students’ development. Through music education for students, they can experience beauty, feel beauty, find beauty from it, and can better develop their ability to appreciate and create beauty. Then these also need us teachers to lead and guide students to experience music. However, the survey found that many teachers are not able to motivate students to learn music in the classroom, making many students gradually lose interest in learning music, resulting in a situation where many students like music but do not like to take music lessons. In fact, this is closely related to the teacher’s teaching style, the single teaching style, teaching methods of boring are the reasons that can not stimulate students’ interest in learning music. Therefore, the use of game teaching method in teaching has been implemented and paid more attention in recent years, and games are not only used in early childhood classrooms, but also started to be widely used in elementary school classrooms. This paper is based on the literature method as a support for the theoretical aspect and understands other teaching methods about game teaching, based on which the practice of gamification teaching of music in elementary school is studied. This paper also uses case study method, field observation method and interview method to experience the classroom of game-based teaching first hand and also find out the problems encountered in the implementation of game-based teaching. In this paper, we will analyze and summarize the best cases and make suggestions for the problems encountered in practice, hoping to make music gamification teaching more efficient in the classroom, so that it can bring into play the desired effect, thus inspiring students to be active in the music classroom, to love music, to gradually improve their creative ability and imagination, to understand the excellent traditional culture, and to achieve the purpose of nurturing people. thus achieving the teaching purpose of nurturing people.